Passivation of Detector‐Grade Float Zone Silicon with Atomic Layer Deposited Aluminum Oxide. Issue 17 (30th July 2019) - Ott, Jennifer; Pasanen, Toni P.; Repo, Päivikki; Seppänen, Heli; Vähänissi, Ville; Savin, Hele
Abstract : Silicon radiation and particle detectors are traditionally passivated with thermal silicon dioxide. It has been shown that aluminum oxide (Al2 O3 ) films provide better surface passivation due to their high negative charge, but studies on Al2 O3 surface passivation are usually performed on low‐resistivity substrates. Herein, the passivation of high‐resistivity, detector‐grade float zone silicon (FZ‐Si) with Al2 O3 is studied, with a specific emphasis on the effect of post‐annealing temperature on carrier lifetimes and film properties. It is confirmed that Al2 O3 provides excellent surface passivation also on high‐resistivity FZ‐Si substrates, with a low interface defect density of around (2–4) × 10 11  cm −2  eV −1 and a high negative oxide charge of 1 × 10 12 to 3 × 10 12  q cm −2, when post‐annealed at temperatures of up to 450–500 °C. In addition, high‐resistivity samples are studied for the phenomenon of bulk lifetime degradation occurring at typical post‐annealing or metal sintering temperatures, which has been reported for low‐resistivity FZ‐Si. At post‐annealing temperatures of >500 °C, reduced bulk lifetimes are observed if the substrates did not receive high‐temperature treatment prior to surface passivation. Furthermore, it is noticed that n‐type samples exhibit lower bulk lifetimes even when a high‐temperature treatment is performed, which indicates a connection between FZ‐Si bulk lifetime degradation and doping type. Abstract : Passivation of detector‐grade float‐zone (FZ) silicon with aluminum oxide (Al2 O3 ) is studied, focusing on the effect of post‐annealing temperature on carrier lifetimes and film properties. It is confirmed that Al2 O3 provides excellent surface passivation on high‐resistivity FZ‐Si substrates. Bulk lifetime degradation during low‐temperature annealing can be prevented by high‐temperature treatment only in p‐type substrates.